Answer:
Line S
Step-by-step explanation:
Answer:
3x³ + x² - 2
Step-by-step explanation:
a) 3(x squared plus 3x cubed - 2)
x squared = x²
3x cubed = 3x³
3(x squared plus 3x cubed - 2)
= 3(x² + 3x³ - 2)
= 3x² + 9x³ - 6
Rearrange according to power
= 9x³ + 3x² - 6
When the expression is divided by 3, it is equivalent to
3x³ + x² - 2
8.05 x 10^8 - 9.16 x 10^6
= 10^6 (805 - 9.16)
= 795.84 x 10^6
= 7.9584 x 10^8
Answer:
0.926
Step-by-step explanation:
5/12 as a decimal is 0.416 and
5/9 as a decimal is 0.5 repeating
You just have to turn the fraction into a decimal and
add those together.
So your final equation would be 0.416+0.5
You have to move your variables around.<span />